The Sustainability of Cultural Diversity in the Workplace: Cultural Values and Intercultural Mindset - Tompos, Anikó; Ablonczy-Mihályka, Lívia (European Journal of Sustainable Development, 2018)
The last two decades saw the emergence of culturally diverse workplaces in Hungary. Researchers usually agree that cultural heterogeneity is an asset and contributes to the sustainability and competitive advantage of firms provided some conditions are met, that is multiple identity workgroups in themselves do not automatically bring positive benefits. Effective work across cultural differences necessitates an increase in cross-cultural intelligence and competence and parallel to this, a decrease in ethnocentrism. The purpose of the paper is to present and discuss the findings of a questionnaire survey (N=367), which set out to map out how Hungarian companies and enterprises manage cultural diversity and to measure business actors’ cultural sensitivity. In particular, it looks at differences between generations X and Y in terms of their intercultural mindset, i.e. their thinking, emotions and attitudes towards diversity. The study concludes that Hungarian businesspeople who work with people of different cultural backgrounds, regardless of age, do not display the ethnocentric and exclusionary attitudes which characterise the society and seem to have sufficient levels cross-cultural intelligence to meet the cultural diversity challenge. Keywords: cultural diversity, generations, intercultural mindset, sustainability